2012
DOI: 10.3389/fpsyt.2012.00058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Frontal Transcranial Direct Current Stimulation on Emotional State and Processing in Healthy Humans

Abstract: The prefrontal cortex is involved in mood and emotional processing. In patients suffering from depression, the left dorsolateral prefrontal cortex (DLPFC) is hypoactive, while activity of the right DLPFC is enhanced. Counterbalancing these pathological excitability alterations by repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS) improves mood in these patients. In healthy subjects, however, rTMS of the same areas has no major effect, and the effects of tDCS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
101
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 39 publications
13
101
0
1
Order By: Relevance
“…tDCS of the left DLPFC and the right frontopolar cortex improves identification of faces displaying nonneutral mimics independent of stimulation polarity, as compared to sham stimulation (Fig. 2) [70] . Moreover, emotionally aversive faces are rated less unpleasant with anodal stimulation of the left DLPFC [72] .…”
Section: Emotional Processesmentioning
confidence: 96%
“…tDCS of the left DLPFC and the right frontopolar cortex improves identification of faces displaying nonneutral mimics independent of stimulation polarity, as compared to sham stimulation (Fig. 2) [70] . Moreover, emotionally aversive faces are rated less unpleasant with anodal stimulation of the left DLPFC [72] .…”
Section: Emotional Processesmentioning
confidence: 96%
“…Disgust instead of angry faces were used because current research points to a greater threat perception for disgust faces (e.g., Amir et al, 2005). Moreover, a previous study testing effects of tDCS over left DLPFC have demonstrated improvements in the attentional detection of both happy and disgust faces (Nitsche et al, 2012). Therefore, this set was considered ideal to test whether tDCS over right DLPFC leads to valence-specific or general attentional disengagement impairments.…”
Section: Attentional Engagement-disengagement Taskmentioning
confidence: 99%
“…However, recent studies on lateralized effects of neurostimulation over the left DLPFC have shown general effects in implementing attentional control for all emotional information rather than specific effects for negative information. Nitsche et al (2012) found that anodal tDCS compared to sham stimulation over left DLPFC had temporal effects in improving attentional detection of both disgusted and happy faces. These findings speak against the traditional view on valence lateralization.…”
mentioning
confidence: 99%
“…Nitsche et al 2012;Peña-Gómez et al 2011;Plazier et al 2012;Vanderhasselt et al 2013), although Fregni et al (2008) completed the final evaluation approximately 10 min after stimulation cessation, while Tadini et al (2011) Batsikadze et al 2013). It is possible that the convention timing of re-assessment following tDCS does not allow for a sufficient period to detect tDCS-induced modulations of mood.…”
Section: Discussionmentioning
confidence: 99%